Synthesis Of Carbonate-Substituted Hydroxyapatite By A Mechanical Activation Method - Tram, Nguyen Xuan Thanh (2010)
A mechanical activation method was used to produce a carbonate-substituted hydroxyapatite powder (CHAp) using CaHPO4.2H2O and CaCO3 as starting materials. The calcium-to-phosphorous molar (Ca/P) ratio of reactants was 1.67. Milling was performed in a sealed agate vials and balls with various parameters to optimize the process. The results showed that processing efficiency was governed by milling time, ball-to-powder weight ratio (BPR), milling speed and milling environment. The optimum parameters are as follows: milling duration of 24 hours, BPR of 10:1, milling speed of 400 rpm and dry milling. Based on these optimum parameters, subsequent milling of reactants at Ca/P ratios of 1.85 and 2.00 were also investigated to evaluate the effect of carbonate content on the properties of CHAp. Thermal behaviour of CHAp powders with different carbonate contents depicted that the substitution of carbonate ions for phosphate group enhanced the thermal stability of apatite.